Flood risk modeling due to the ocurrence of maximum discharges from the Santa river, Challhua sector, Huaraz-Ancash - Tinoco Meyhuay, Tito (2019)
The objective is to identify the areas exposed to risk by flood due to the occurrence of maximum discharges of river Santa in the sector of Challhua, Huaraz. Through the probabilistic method of Gumbel, it was determined the base flow and the maximum flow of the studied area for dierent return periods (5, 10, 50, 100 y 200 years). Besides, the levels of water and the flood areas were determined through the programs HecRAS and HecGeoRAS, whose results ranged between 371,49 square meters for the base flow and 1927,08 square meters for a return period of 200 years. In addition, it was determined that 91 houses and 18 market modules present very high vulnerability, 91 houses and 20 market modules high vulnerability, 94 houses medium vulnerability and 91 houses low vulnerability. The overlap of the flood areas and the vulnerability map determined the risk, finding that the 8,2 % of houses and the 47,4 % of market modules are in very high risk, the 41,1 % of houses, the 52,6 % of market modules and the 100 % of sportif infrastructure are in high risk, while the 25,6 % of houses are in medium risk and the 24,8 % of houses in low risk